The Now-Defunct ResearchGate Score and the Extant Research Interest Score: A Continued Debate on Metrics of a Highly Popular Academic Social Networking Site - Teixeira da Silva Jaime A. (Open Information Science)
Academics might employ science social media or academic social networking sites (ASNSs), such as ResearchGate (RG), to showcase and promote their academic work, research, or published papers. In turn, RG provides usage statistics and performance metrics such as the now-defunct RG Score and the Research Interest Score (RIS) that offer a form of recognition about a researcher’s popularity, or how research is being used or appreciated. As part of a larger appreciation of how ASNSs contribute to knowledge sharing, in this article, the RG Score is reappraised, reflecting on why this metric may have been abandoned while reflecting on whether RIS is any better as an author-based altmetric. Similar to the RG Score, RG does not transparently indicate the precise equation used to calculate RIS, nor is any rationale provided for the weighting of its four factors (other reads, full-text reads, recommendations, and citations), which carry a relative weighting of 0.05, 0.15, 0.25, and 0.5, respectively. Ultimately, the responsible use of RG’s altmetrics lies in users’ hands, although caution is advised regarding their use to formally characterize or rank academics or research institutes.